Structural Reforms and Macroeconomic Performance : Initial Considerations for the Fund. (Policy Papers; Policy Paper ;, 2015)
Structural policies have become a prominent feature of today's macroeconomic policy discussion. For many countries, lackluster economic growth and high unemployment cloud the outlook. With fewer traditional policy options, policymakers are increasingly focused on the complementary role of structural policies in promoting more durable job-rich growth. In particular, the G20 has emphasized the essential role of structural reforms in ensuring strong, sustainable and balanced growth. Against this backdrop, the 2014 Triennial Surveillance Review (TSR) called for further work to enhance the Fund's ability to selectively provide more expert analysis and advice on structural issues, particularly where there is broad interest among member countries. The purpose of this paper is to engage the Board on staff's post-TSR work toward strengthening the Fund's capacity to analyze and, where relevant, offer policy advice on macro-relevant structural issues.